Substituição parcial do farelo de soja por ureia encapsulada para vacas leiteiras alimentadas com cana de açúcar - Geraldo Filgueiras Neto (2011)
Aiming to evaluate the dry matter intake (DMI), production, milk composition, production of microbial protein and rumen parameters of dairy cows F1 girolando partially replaced soybean meal diet for urea or encapsulated urea (Optigen®II). The animals were divided randomly into three treatments (Control, Optigen and Urea), totaling 18 animals tested for the reversal of the performance experiment and three fistulated cows in 3x3 Latin square for the evaluations of rumen fluid. Diets were formulated to be isonitrogenous (15.5%) and isocaloric. About 13% of total protein was derived from non-protein nitrogen (NPN) of Optigen ® II or urea. There was no significant difference in milk production (28.17 kg / day), dry matter intake (22.17 kg / day) and solid production. The numerical treatment Optigen was superior in all parameters with the exception of DMI, which was intermediate. The contrast Optigen x Urea were higher in favor of Optigen for variable production and milk composition did not differ for the concentration of urea nitrogen in milk (17.54 mg / dl), while the urea nitrogen in plasma was significantly lower for the Optigen in the control and urea 4 and 6 hours after feeding. The treatments were equivalent in the excretion of purine derivatives, urine production, feed efficiency and nitrogen utilization. The evaluation of rumen fluid showed an increase of ammonia nitrogen and volatile fatty acids two hours after meals. The experiment showed that the partial replacement of soybean meal by Optigen®II were better than the replacement by urea, did not affect animal performance and reduced levels of urea nitrogen in plasma.